PREDOMINIO DE LOS MEDIOS DE COMUNICACIÓN RADIALES EN LA CALIDAD DE VIDA DE LOS HABITANTES DE LA COOPERATIVA NUEVA ESPERANZA DEL CANTON BUENA FE, AÑO 2022. - Arreaga Salazar, Samuel Joel (2022)
The purpose or objective of this research is to analyze the impact of the predominance of the radio media and the information received by the inhabitants of the Nueva Esperanza Cooperative of the Buena Fe canton, year 2022. The study was based on a bibliographic review of topics related to the problem under study. Its methodology was based on a study of mixed character since interviews were conducted with the journalists involved in the case study and, at the same time, surveys were conducted with the inhabitants of the cooperative. In addition, field research was carried out to gather information in situ. Thanks to this, the results of the research were determined, in which it is important to emphasize that not all journalists have updated knowledge about good practices in their profession and therefore the inhabitants feel affected in their broadcasts, hence the need to create the proposal based on training to improve the practices of journalism and thus achieve a high level of perception in the inhabitants.